Telecommunications postage stamp - Wong, Ding Jie (2015)
This report will cover one part of a two-part GPS logistics tracking project, and will focusing on minimizing the size of the hardware. This report aims to introduce both new, and established, technologies that can result in reducing the size of a working GPS Tracking Device and back-end system for logistics. New technology discussed is the Sigfox system, which is only found in Europe, while old technologies would be the Global Positioning System(GPS), Global System for Mobile communication(GSM) The back-end system, the other part of the project comprises of SQL databases and an Android platform serving as an SMS server. It also aims to detail the student's part in building the prototype, and the process of proposing a final design schematics. The finalized design was made with the considerations that is discussed in the report, and based on the prototype modules that was used.